Appropriation of geek culture by scientific disclosure –Nerdologia Channel - Cardoso, João Batista Freitas (2022)
Seeking to stimulate a bigger reach of scientific divulgation tothe non-specialist public, some actions have been noticed on online media. Some of these actions are aimed at young people and teenagers interested in pop culture and digital culture content, such as the geek audience. As an example of these is Nerdologia, a channel from YouTube, which covers scientific issues that are discussed by experts, with elements of language and narrative from pop culture, in particular, from geek culture. Such communication strategy is based, in large part, on different forms of image appropriation. The main objective is to discuss the different forms of appropriation of geek culture by Nerdologia channel.